A new finding of a uniquely large population of Anacamptis morio (Orchidaceae) on the Left-Bank Ukraine - Shevchyk, Vasyl L.; Solomakha, Igor V.; Shevchyk, Oksana V.; Dvirna, Tetyana S.; Solomakha, Volodymyr A.; Shevchyk, Taras V.; Fitsailo, Tetyana V. (Biodiversity: Research and Conservation, 2020)
The paper presents the results of the research of local population of Anacamptis morio (L.) R. M. Bateman on the territory of the Left-Bank Ukraine. The size of this population was estimated at about 250-300 thousand individuals. The average density of individuals per 1 m2 is 12, while in terms of age structure, dominate individuals in the generative stage (70-75%). A. morio inhabits fresh, forest-meadow biotopes. Its populations are found in fresh eutrophic and moist mesotrophic meadows and in coastal floodplain forests. This species is a part of vegetation of the Koelerio-Corynephoretea and Molinio-Arrhenatheretea classes. Considering the characteristics of the investigated A. morio population and its habitat we assert that the studied territory is unique, valuable and perspective for the creation of a nature reserve.